Population Density, CO2 Emission and Energy Consumption in Pakistan: A Multivariate Analysis - Muhammad, Faqeer; Karim, Rehmat; Muhammad, Khair; Asghar, Amna (International Journal of Energy Economics and Policy, 2020)
The objective of the research is to re-examine the influences of population density, energy consumption on CO2 emission in Pakistan. In addition, the effect of the growth and trade is also discovered in the study using Fully Modified Least Square (FMOLS) method from 1990 to 2014. Further, robust analysis is carried by utilizing Dynamic Ordinary Least Square (DOLS) method. Initially, unit root test is tested by Augmented Dicky Fuller test and Phillips-Perron (PP) test, and long run relationship is studied by Johansen Cointegration test. The outcomes of the research show the influential contribution of population density, energy consumption on environmental decay in Pakistan. Likewise, the other elements, which plays significant role in pollution, are growth and trade. The results of the robustness check also endorse population density and energy consumption are contributing CO2 emission in Pakistan. Therefore, the study recommends that population control should be the target of the government and limit and introduce environmentally friendly sources of energy. Keywords: Population density, energy consumption, CO2 emissions, Pakistan. JEL Classifications: Q4, Q42 DOI: https://doi.org/10.32479/ijeep.10341